2016
DOI: 10.1002/art.39733
|View full text |Cite
|
Sign up to set email alerts
|

Prion‐like Aggregation of Mitochondrial Antiviral Signaling Protein in Lupus Patients Is Associated With Increased Levels of Type I Interferon

Abstract: Objective Increased levels of Type I interferon (IFN-I) and IFN-I-regulated genes are found in patients with systemic lupus erythematosus (SLE) and may be central to its pathogenesis. The mitochondrial adaptor protein MAVS is a key regulator of IFN-I that undergoes a dramatic prion-like aggregation and self-propagates the activation signal from viral RNA to amplify downstream IFN production. We wondered if such MAVS aggregates might play a role in the sustained increased production of IFN-I in SLE. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Interestingly, the patients with detectable cGAMP had a higher SLEDAI score than patients without activation of the pathway (70). With regard to RNA sensors, aggregation of MAVS has been demonstrated in patients with SLE which may be associated with oxidation of mtDNA (71, 72). Hasan et al (73) reported that TBK1 (a protein downstream of cGAS as well as RLR) mRNA expression was significantly increased in SLE patients, especially in monocytes.…”
Section: Nucleic Acids Stimulate Pattern Recognition Receptors To Indmentioning
confidence: 99%
“…Interestingly, the patients with detectable cGAMP had a higher SLEDAI score than patients without activation of the pathway (70). With regard to RNA sensors, aggregation of MAVS has been demonstrated in patients with SLE which may be associated with oxidation of mtDNA (71, 72). Hasan et al (73) reported that TBK1 (a protein downstream of cGAS as well as RLR) mRNA expression was significantly increased in SLE patients, especially in monocytes.…”
Section: Nucleic Acids Stimulate Pattern Recognition Receptors To Indmentioning
confidence: 99%
“…Studies have shown that persistent MAVS aggregation may be associated with the occurrence of autoimmune diseases such as systemic lupus erythematosus. Further, the sustained expression of IFN and its regulatory genes and unsuppressed signals, will eventually result in tissue damages(56).K27-linked ubiquitination by the E3 ubiquitin ligase TRIM21 also has a positive regulatory effect on MAVS. Viral infection upregulates the expression of TRIM21, thereby promoting the…”
mentioning
confidence: 99%
“…The study of Dominguez-Gutierrez et al showed overexpression of ADAR in Systemic Lupus Erythematosus (SLE) patients [35]. In addition, decreased MARCH5 protein might account for the constant Mitochondrial Antiviral-Signaling Protein aggregations and abnormalities of type I interferon levels in SLE patients [25]. Current study did not indicate ADAR and MARCH5 as miR-652-5p targets in luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 52%
“…Using the Venn's diagram (Venny 2.1.0, http://bioinfogp.cnb.csic.es/tools/venny) we identified 22 immune response genes. For further investigation 2 autoimmune related genes: Adenosine Deaminase, RNA Specific (ADAR) [24] and Membrane Associated Ring-CH Finger Protein 5 (MARCH5) [25] were selected. The sequences of miRNA bindings sites in 3'UTR of target genes were verified by PITA-Segal lab software (https://genie.weizmann.ac.il).…”
Section: Mirna Target Gene Predictionmentioning
confidence: 99%